Satanizing Herod: Two Episodes of Mat 2,13-16’s «Wirkungsgeschichte» and its Intertextuality with Revelation 12 - Cardozo Mindiola, Cristian (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2023)
Although Mt 2,13-16 holds Herod accountable for his murderous deeds, several early Christian writers thought that he acted under the influence of Satan. Among them, Tyconius and Oecumenius are of special consideration since they were the first to provide a hermeneutical framework that evinced the assertion. Therefore, this article intends to answer two questions: Why did Tyconius and Oecumenius think Satan was under the influence of Satan in Mt 2,13-16? and how did they reach this conclusion? To do so, this article employs Wirkungsgeschichte as its methodology. Accordingly, the satanization of Herod is the byproduct of reading Mt 2 and Ap 12 intertextually since the actions of the former are now seen under the light of the apocalyptic dragon.